Web-based clothing and fabric stock data processing information system at PT. Crevis Tex Jaya - Denada Fatimah Zahra; Desy Yulianti (Institute of Computer Science (IOCS), 2023)
Technology in the era of globalization plays an important role in supporting daily life activities, both in the fields of education, business, entertainment, government, and others. Computers as a manifestation of technology facilitate human work with one of its tools, namely information systems commonly used for data processing, but many companies currently still use manual data processing which has the potential to cause data management errors. The proposed solution to the problem requires the provision of computer equipment and human resource training. PT Crevis Tex Jaya, famous for its clothing and fabric business, must have an information system to handle clothing and fabric inventory data that is computerized, MySQL is used as a database server to facilitate data query. The following study produces an apparel inventory data processing system that supports the implementation of data processing to minimize errors, improve work efficiency, and speed up reporting.